Distribution of Hypertension Cases Among the Productive-Age Population in the Wanggudu Raya Community Health Center Catchment Area, Asera District, North Konawe Regency - Devi Savitri Effendy; Rahmi Fauziyah; Lustina Lustina; Normalisa Normalisa (Journal of Epidemiology and Health Science, 2026)
Background: Hypertension is one of the most common cardiovascular diseases experienced by people around the world. The occurrence of hypertension is influenced by various risk factors such as age, gender, occupation, and level of education. Objective: To describe hypertension cases at Wanggudu Raya Health Center based on gender, age, occupation, and education variables. Methods: This research is descriptive in nature and was carried out at Wanggudu Raya Health Center in 2024. The data used were secondary data obtained from medical records of hypertension patients during that year. The population in this study amounted to 193 people. Results: The characteristics of hypertension sufferers were dominated by female patients aged 45–59 years. The majority of respondents were housewives with a senior high-school education level. Conclusion: The population most affected by hypertension in the Wanggudu Raya Health Center working area consisted of women aged 45–59 years, working as housewives, and having a senior high-school education level. Keywords: Cardiovascular Diseases, Hypertension, Risk Factors, Educational Status, Medical Records